Reflection and Refraction of Shear Horizontal Waves in Peridynamic Medium - Xiaolong Zhang; Yaru Lu; Liyu Chen; Zhenying Xu (Shock and Vibration, 2020)
This work uses peridynamic theory to obtain the internal force density of a shear horizontal (SH) wave, which is only connected with shear modulus. We then established the reflection equation of a SH wave in peridynamic medium based on the force boundary condition of the SH wave at the virtual boundary layer. The SH wave reflection characteristic in peridynamic medium is similar to the results of traditional theory, which was verified by simulations and experiments in steel plates. The refraction characteristics of a SH wave in peridynamic medium were obtained based on the continuity of the force and the displacement at the refraction point. These features established the relationship between bonds and wave angle. The refraction and reflection characteristics of a SH wave in a peridynamic medium were also verified by numerical simulations and experiments in a welded structure.